Immunotoxin Lesion of the Cholinergic Nucleus Basalis Causes Aβ Deposition: Towards a Physiologic Animal Model of Alzheimer's Disease - Beach, T.G.; Walker, D.G.; Sue, L.I.; Scott, S.; Layne, K.J.; Newell, A.J.; Potter, P.E.; Durham, R.A.; Emmerling, M.R.; Webster, S.D. (Current Medicinal Chemistry - Immunology, Endocrine & Metabolic Agents, 2003)
Transgenic βAPP mice are valid and useful models of Alzheimer's disease (AD) as they effectively recreate Aβ deposition, which is widely regarded as the central pathogenic event in the disease. Transgenic mice do not, however, replicate the initial pathogenic event of the most common form of AD. The majority of AD is not caused by any of the gene mutations employed to create these mice. As cortical Aβ deposition is a common, if not universal, occurrence in many mammalian species, its cause is likely to lie within the physiologic process of aging. We have created an animal model of Aβ deposition by inducing cortical cholinergic deafferentation, a well-known aging change, in the brains of young rabbits. Lesioning the cholinergic nucleus basalis magnocellularis (nbm) results in cortical cholinergic deafferentation and cortical Aβdeposition. The Aβ deposits are primarily vascular, with occasional perivascular plaques. The specificity of this change for cholinergic processes has been demonstrated by the reduction of lesion-induced Aβ deposition by cholinergic therapy with AF267B, an m1-selective muscarinic agonist, and physostigmine, an acetylcholinesterase inhibitor, and by showing that lesioning of the noradrenergic locus ceruleus does not cause Aβ deposition. Significant decreases in cortical synaptic antigen density occur at 6 months post-lesion. Examination of longer survival periods has been complicated by regeneration of cortical cholinergic afferents but repetitive nbm lesions are expected to overcome this obstacle. Agerelated degeneration of the nbm in humans may be a major contributor to Aβ deposition in normal aging and AD.
Keywords: deposition